Molecular Identification of Carnosine N-Methyltransferase as Chicken Histamine N-Methyltransferase-Like Protein (HNMT-Like) - Drozak, Jakub; Chrobok, Lukasz; Poleszak, Olga; Jagielski, Adam K.; Derlacz, Rafal (PLOS ONE, 2013)
Anserine (beta-alanyl-N(Pi)-methyl-L-histidine), a naturally occurring derivative of carnosine (beta-alanyl-L-histidine), is an abundant constituent of skeletal muscles and brain of many vertebrates. Although it has long been proposed to serve as a proton buffer, radicals scavenger and transglycating agent, its physiological function remains obscure. The formation of anserine is catalyzed by carnosine N-methyltransferase which exhibits unknown molecular identity. In the present investigation, we have purified carnosine N-methyltransferase from chicken pectoral muscle about 640-fold until three major polypeptides of about 23, 26 and 37 kDa coeluting with the enzyme were identified in the preparation. Mass spectrometry analysis of these polypeptides resulted in an identification of histamine N-methyltransferase-like (HNMT-like) protein as the only meaningful candidate. Analysis of GenBank database records indicated that the hnmt-like gene might be a paralogue of histamine N-methyltransferase gene, while comparison of their protein sequences suggested that HNMT-like protein might have acquired a new activity. Chicken HNMT-like protein was expressed in COS-7 cells, purified to homogeneity, and shown to catalyze the formation of anserine as confirmed by both chromatographic and mass spectrometry analysis. Both specificity and kinetic studies carried out on the native and recombinant enzyme were in agreement with published data. Particularly, several compounds structurally related to carnosine, including histamine and L-histidine, were tested as potential substrates for the enzyme, and carnosine was the only methyl group acceptor. The identification of the gene encoding carnosine N-methyltransferase might be beneficial for estimation of the biological functions of anserine.